Pengaruh Rasio Magnesia-Kalsia terhadap Morfologi dan Kekuatan Tekan Aluminium Foam, Al-1000 dengan Foaming Agent Kalsium Karbonat - Sutarno Sutarno; Mahardika Rizkiana; Kusharjanto Kusharjanto (Badan Kerja Sama Pendidikan Metalurgi dan Material (BKPMM), 2018)
The vehicle weight have correlation with fuel oil consumption, increasing gas emission CO2, and global warming has encouraged the development of light materials and eco-friendly environment likes aluminium foam and magnesium alloys. This aims research is to study the fabrication of aluminium foam Al-1000 with calcium carbonate as a foaming agent and the effect of magnesia-calcia ratio as stabilizer to morphology and compressive strength. In the fabrication of aluminium foam, magnesia-calcia is established to 2% weight and varying the ratio of calcia-magnesia of 0:16 ; 2:14 ; 4:12 ; 6:10 and 8:8, and calcium carbonate is required to 3% weight fraction and operation temperature is 770oC. The results show that the higher porosity is 83.23% with relative density 0.17; pore diameter is 3.97mm, pore wall thickness is 17.39 micron, rounded is 0.84 and lowest compressive strength is 3,14 MPa occurred at magnesia-calcia ration is 0:16, while the lowest porosity is 79.38% with relative density 0.21; pore diameter is 3.71; wall thickness is 101 µm and rounded is 0.84 and compressive strength is 6.611 MPa at magnesia-calcia ratio 4:12.